Tooth movement and root resorption; The effect of ovariectomy on orthodontic force application in rats - Irin Sirisoontorn (2018)
Objective: To quantify the amount of tooth movement and orthodontically induced root resorption (OIRR) in ovariectomized rats. Materials and Methods: Five 10-week-old female Wistar rats undergoing ovariectomy (OVX) were investigated as the experimental group, and the other five without ovariectomy served as the control group. Four weeks after ovariectomy, 25-g nickel-titanium closed-coil springs were applied mesially to the maxillary left first molars. Micro-computed tomography was taken at day 0, 1, 3, 7, 14, 21, and 28. At day 28, the molars were extracted. The surface area of root resorption craters, depth, and volume were measured using electron and laser scanning microscopes. Results: Tooth movement gradually increased with time throughout 28 days. There was a significant difference in the amount of tooth movement between the control group and the OVX group. For OIRR, the OVX group showed wide and shallow root resorption craters scattered on the mesial root. The deep resorption craters were observed on the distal roots distributed in the cervical, middle, and apical thirds of the roots. Statistically significant differences were found between the control and the OVX groups in the depth and the volume of root resorption craters in the distal roots and the total volume of root resorption craters in all three roots. Conclusion: Ovariectomy affected not only tooth movement but also OIRR. Tooth movement in the OVX group was more rapid than the control group. Furthermore, the amount of OIRR in the OVX group was more severe than the control group. © 2011 by The EH Angle Education and Research Foundation, Inc.